Religious Tourism on the Example of Nation Pilgrim Places in Slovakia (Patronages of the Virgin Mary) - Judák, Viliam; Petrikovičová, Lucia; Akimjak, Amantius (Journal of Education Culture and Society, 2022)
Aim. Pilgrimage thus belongs to the oldest non-economic forms of migration and is a phenomenon that has intertwined throughout the history of religions. The aim of the article is to emphasize the important position of religious tourism as one of its forms. Based on the deep-rooted tradition of wandering in Slovakia, characterize important places of pilgrimage of national and perhaps partly international significance. Method. Terrain reconnaissance together with analysis of archival and parish documents. Results. Numerous Marian temples and chapels testify to the Marian veneration in Slovakia. Of the 5925 known patronages of churches and chapels (even those that have disappeared) in Slovakia, 1762 are dedicated to the Virgin Mary. Of these Marian patrons, 329 are consecrated by the Seven Sorrows of Our Virgin Mary. The result of field research is an analysis of six pilgrimage sites of national importance in Slovakia. Conclusion. Slovakia is a strongly Christian country with a tradition of wandering, as evidenced by many local and regional pilgrimage sites. Pilgrimage sites are understood as contact points that God has marked, they are the intersections where the ways of God meet the ways of people. There are mostly Marian pilgrimage sites in Slovakia and six of them (Marianka, Staré Hory, Levoča, Šaštín, Nitra, Ľutina) are of national importance.